Tegenlicht op Pasolini - Dullaart, Leo; Hekma, Gert; van Kerkhof, Marty; Maasen, Thijs; Sanders, Stephan; Verstraeten, Paul (Den Haag : De Woelrat, 1982)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie